Direito e sustentabilidade ao encontro das diversidades no meio ambiente ecologicamente equilibrado: os direitos da sociobiodiversidade - Cavalheiro, Larissa Nunes (2015)
During its existence, humanity and its bond with the environment is affected by different perceptions of value given to nature. First, as a means harboring natural resources for survival, human and non-human inevitably depend on the availability and quality of natural elements. What happens is that the human capacity exceeds the desire for mere existence and starts to develop their social and economic pretensions, negatively impacting the environment, compromising the balance necessary for Life as a whole. This apprehension different perceptions are established, first an anthropocentric view - the world of humanity - referencing human interests above all, going through more pronounced ecological concepts - humanity in the world - at which point is highlighted the environmental balance as the biggest value. But both perceptions do not address the complex and dynamic human-environment relationship, reflected in this work on the concept of sociobiodiversity, ie the sustainable lifestyles deriving from traditional peoples knowledge in the management of biodiversity. From this scenario, beyond the natural and cultural diversity, reveal themselves the rights of diversity - the Rights of Sociobiodiversity. Thus, the increasing development of humanity to the encounter sustainability to guarantee the constitutional legal ideal of this - the right to an ecologically balanced environment - is oriented a socio-environmental reflection of recognition, guarantee and protection of these rights. To this end, one must overcome the apprehension of the rich scenario of mega-diverse and multicultural countries like Brazil, just under the bias of economic social biodiversity potential, otherwise the maintenance of inequality is maintained through a human-environmental exploitation, North - capital and technology - towards the South - biodiversity and multiculturalism of knowledge. Thus, it sets out a (re) significance of sustainability from ecological and legal implications of sociobiodiversity, in order to reinforce a development paradigm in line with the diversity - natural, cultural and legal - in the same way that will the Law to be reflective on the rights of Sociobiodiversity emerging highlighted in an intercultural dialogue.